Fecal carriage of Extended Spectrum β-Lactamases (ESBL) Producing Escherichia coli and Klebsiella spp. among School Children in Pokhara, Nepal - Baral, Bharat Prasad; Koirala Sharma, Binita; Gurung, Krishna; Gurung, Ram Raja; Supram, Hosuru Subramanava; Bhattachan, Balkrishna (Nepal Journal of Biotechnology, 2019)
Extended-spectrum β-lactamases (ESBL) producing microbes in recent years have been a major problem in developing countries like Nepal, with limited treatment options. This study aimed to determine the prevalence of ESBL producing E. coli and Klebsiella spp. in school children in Pokhara, Nepal. The study was conducted from June to October, 2015 at the microbiology laboratory of Manipal Teaching Hospital, Pokhara, Nepal. Antibiotic Susceptibility Test (AST) was done after isolation and identification of bacterial isolates. Then, presence of ESBL enzymes in E. coli and Klebsiella spp. were tested by combination disc diffusion test using cefotaxime and ceftazidime alone and with clavulanic acid. Out of total 309 school children, 211 (68%) bacterial isolates were detected from stool samples. Among them, E. coli and Klebsiella spp. were detected in 97 (46%) and 39 (19%) stool samples respectively. Bacteria isolated from 14 (5%) stool samples were multi-drug resistant (MDR) positive. After applying combined disk method, 88 (29%) isolates were found to be ESBL producer. Emerging prevalence rate of ESBL producing E. coli and Klebsiella spp. are major problem in medical history. Therefore, rapid need of surveillance for effective management of such MDR-strain is required.